Pengaruh Pembelajaran Berdiferensiasi Bermodel Project Based Learning Terhadap Kemampuan Menulis Teks Puisi Pada Fase D (VIII) SMP - Gea, Cindi Kristiani; Sitorus, Pontas J.; Simanjuntak, Harlen (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
This research was conducted at SMP Negeri 11 Medan with the aim of finding out the effect of differentiated learning using the Project Based Learning model on phase D (VIII) students of SMP Negeri 11 Medan. This research uses a quantitative experimental research method with a Two Group Posttest Only Design. The population of this study was all class VIII, totaling 300 students. This research involved two classes, namely the control class and the experimental class. The data analysis techniques used in this research were normality tests, homogeneity tests and hypothesis tests. To obtain data, the assignment to write poetry texts was used from the analysis obtained from the students' ability to write poetry texts at K VIII SMP Negeri 11 Medan using differentiated learning with the Project Based Learning model. The lowest score was 60 and the highest score was 95 with an average of 80.17. Based on the results of the calculations carried out, tcount = 9.82456 and ttable = 1.67155 with a significance level of 5% with df= (N1+N2)-2, df which is 58. From df 58, a significance level of 5% = 1.67155 is obtained based on the calculations that have been made. carried out, it can be seen that Tcount>Ttable is 9.82456>1.67155. Thus the initial hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. So it will be stated that differentiated learning using the Project Based Learning model has an effect on the ability to write poetry texts.